Factors Affecting the Use of Information and Communication Technology in Agriculture: Insights from Different Agro-Ecological Zones of Nepal - Mishra, Binayak Prakash (Journal of the Institute of Agriculture and Animal Science, 2024)
ICT tools are very crucial in modern agriculture to address all the information needs of farmers. A logit model was applied to assess the factors influencing the use of ICT in agriculture across different agro-ecological zones of Nepal by using the household survey of 210 farmers consisting 70 farmers from each district (Chitwan, Lamjung and Jumla). Pretested semi-structured questionnaire survey was taken in the year 2022. The findings of study revealed that the usage of ICT tools in the study area was mostly determined by the socio-economic and institutional factors. Gender, age and income of farmers affected the probability of use of ICT in farming practices. Additionally, membership to cooperatives, contact to extension agents and training programs related to the operation of ICT tools increases the usage of ICT in agriculture. Thus, government bodies, concerned stakeholders and policy should focus on young male farmers and provide them with proper training and consultation with extension personnel which might be through increment in membership to cooperatives. As income directly influenced the use of such technologies, financial support to initial installation could be the better option for use of ICT in agriculture.